Exploring the Species Diversity of Edible Mushrooms in Yunnan, Southwestern China, by DNA Barcoding - Ying Zhang; Meizi Mo; Liu Yang; Fei Mi; Yang Cao; Chunli Liu; Xiaozhao Tang; Pengfei Wang; Jianping Xu (Journal of Fungi, 2021)
Yunnan Province, China, is famous for its abundant wild edible mushroom diversity and a rich source of the world’s wild mushroom trade markets. However, much remains unknown about the diversity of edible mushrooms, including the number of wild edible mushroom species and their distributions. In this study, we collected and analyzed 3585 mushroom samples from wild mushroom markets in 35 counties across Yunnan Province from 2010 to 2019. Among these samples, we successfully obtained the DNA barcode sequences from 2198 samples. Sequence comparisons revealed that these 2198 samples likely belonged to 159 known species in 56 different genera, 31 families, 11 orders, 2 classes, and 2 phyla. Significantly, 51.13% of these samples had sequence similarities to known species at lower than 97%, likely representing new taxa. Further phylogenetic analyses on several common mushroom groups including 1536 internal transcribed spacer (ITS) sequences suggested the existence of 20 new (cryptic) species in these groups. The extensive new and cryptic species diversity in wild mushroom markets in Yunnan calls for greater attention for the conservation and utilization of these resources. Our results on both the distinct barcode sequences and the distributions of these sequences should facilitate new mushroom species discovery and forensic authentication of high-valued mushrooms and contribute to the scientific inventory for the management of wild mushroom markets.